Significant Reduction in the Incidence of Genital Warts in Young Men 5 Years Into the Danish Human Papillomavirus Vaccination Program for Girls and Women. Issue 4 (April 2016) - Bollerup, Signe; Baldur-Felskov, Birgitte; Blomberg, Maria; Baandrup, Louise; Dehlendorff, Christian; Kjaer, Susanne K.
Abstract : Background: Denmark introduced the quadrivalent human papillomavirus vaccine into the vaccination program for 12- to 15-year-old girls in 2008 to 2009. In 2012, the program was supplemented with a catch-up program for women aged up to 27 years. We evaluated the effectiveness of the Danish vaccination program on the nationwide incidence of genital warts (GWs), after the second catch-up by including information on both hospital treatments and on self-administered treatment with podophyllotoxin. Genital wart incidence was investigated in both sexes; however, the main focus was on potential herd protection of men. Methods: Incident cases of GWs were identified from the Danish National Patient Register and through redemptions of prescription for podophyllotoxin in the Danish National Prescription Registry in 2006 to 2013. Age-specific incidence rates (IRs) were assessed, and estimated annual percentage change (EAPC) was calculated by Poisson regression. Results: Genital wart incidence was either stable or increased in both sexes in 2006 to 2008. After introduction of the vaccination program, GW incidence decreased significantly in women aged 12 to 35 years and men aged 12 to 29 years, with rapid decrease among 16- to 17-year-olds (IRwomen, from 1071 to 58 per 100, 000 person-years [EAPC, −55.1%; 95% confidence interval, −58.7 to−51.2]; IRmen, from 365 to 77 per 100, 000 person-years [EAPC, −36.6%; 95% confidence interval, −40.5 to −32.5] in 2008–2013). Conclusions: We found a significantly decreasing incidence of GWs in women up to 35 years of age after the start of the human papillomavirus vaccination program. A similar pattern was observed for men aged 12 to 29 years, indicating substantial herd protection. Abstract : Since the introduction of a nationwide human papillomavirus vaccination program for girls/women in Denmark, the incidence of genital warts has decreased rapidly not only in women but also in men.